Little Women and Transformative Girl Narrative in China: Translation, Adaptation and Reception - Chang, Shaohua (Ilmu Inovasi Nusantara, 2025)
This study explores the textual transformations of Little Women (1868–69) by Louisa May Alcott in China, focusing on its translations, adaptations, and reception across different historical periods. Despite its initial perception as an educational novel shaping girls' values and behaviors, Little Women has evolved into a text that empowers women, reflecting tensions between patriarchal norms and feminist ideals, as well as between children’s and adult discourse. Drawing on André Lefevere’s manipulation theory and a feminist perspective, this research examines key Chinese translations and adaptations, including Zheng Xiaocang’s 1933 translation, the 1957 Cantonese film adaptation, and Liu Chunying and Chen Yuli’s 2020 translation influenced by Greta Gerwig’s film. The findings reveal that these transformations not only reshape gender narratives but also mirror China’s modernization process and the evolution of Chinese feminism. By analyzing how gender issues in the original text are conveyed and negotiated in different socio-historical contexts, this study highlights the dynamic interaction between literature, translation, and cultural shifts. It further underscores the role of literary adaptation in shaping feminist discourse in China. Future research should explore how translated and adapted literary works contribute to cross-cultural exchanges and evolving gender perceptions